Structure and Mechanical Properties of Titanium Processed by Twist Extrusion and Subsequent Rolling - Tarasov, O. F.; Gribkov, E. P.; Pavlenko, D. V.; Danylenko, M. I.; Altukhov, A. V.; Грибков, Е. П. (Hindawi, 2022)
The article considers one of the combined methods of severe plastic deformation (SPD), which includes twist extrusion (TE) and subsequent rolling. Te use of combined forming methods is promising for industrial use. Titanium grade 1 was used as a material in the experiments. Rolling was carried out in three stages with a decrease in temperature from 350°C to 180°C for a number of passes with one heating. Te accumulated strain degree was e = 4.6 at twist extrusion and e = 3 in rolling. Increasing the reduction per pass decreases the number of heatings and increases the efciency of the rolling process in whole. At the same time, it is necessary to set the maximum processing modes at which recrystallization processes do not occur in the billet. When rolling, the deformation degree in one pass was taken in the range of 5–20% with an increase in successive passes. Te use of such deformation degrees allowed reducing the grain size in titanium grade 1 signifcantly. Twist extrusion reduces the grain size to 300–500 nm. Subsequent rolling allowed reducing the size of structural elements to 50–100 nm and provided a signifcant increase in the mechanical characteristics of the billet material (up to 869 MPa) while maintaining satisfactory ductility (up to 11.6%). It was found that increasing the deformation degree in one pass up to 40% at cross-rolling and simultaneously increasing the temperature to 385°C led to a decrease in the UFG structure quality and reduced strength of the deformable material by starting the dynamic recrystallization process.